(untitled) (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Pandey N, Khanal L, Chapagain N, Singh KD, Bhattarai BP, Chalise MK. 2021. Bird community structure as a function of habitat heterogeneity: A case of Mardi Himal, Central Nepal. Biodiversitas 22: 262-271. Community structure of birds at different habitat types is underexplored in the montane environment of the central Himalaya. Therefore, this study explored bird community structure in different habitat types in Mardi Himal of the Annapurna Conservation Area, central Nepal, and tested association of different feeding guilds with the habitats. Data on the avian richness and abundance were collected in the winter and the summer of 2019 by point count method along the elevational gradient in every 100 m rise and analyzed using ordination methods. A total of 673 individuals of 112 bird species from 35 families under 13 orders were recorded. Among the observed orders and families, the order Passeriformes (77 species) and family Muscicapidae (16 species) were the most dominant. A linear species accumulation curve was obtained in both seasons. Species richness and abundance were found higher at forest edges of mid-elevations and insectivores were the most abundant birds. Frugivorous and carnivorous birds showed no specific association with habitat types, whereas, insectivores and omnivores were more abundant in pastureland and forest, respectively. Our results revealed that the community composition of birds varies with the habitat types and their feeding specialization is one of the major determinants.